1997
DOI: 10.1023/a:1007375114106
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The isolation of Mycobacterium malmoense has for a long time been restricted to few countries of Northern Europe; reports from countries other than Sweden, Great Britain and Finland are rare and the first Italian case report has been published in 1995. Since 1988, however, fifteen strains of M. malmoense have been isolated in Italy, eleven of which in the last two years; of these, ten appeared clinically significant on the basis of medical records. The susceptibility of the strains and the role of high perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Interestingly, the sequence of the hypervariable region A from our type strain was identical to the "genotype 3" profile of a recently published study on a few mycobacterial isolates phylogenetically related to M. simiae (31). The authors of that study concluded that the genotype 3 isolates (n ϭ 2) had an HPLC phenotype similar to that of M. lentiflavum, but conventional tests identified them as M. simiae.…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, the sequence of the hypervariable region A from our type strain was identical to the "genotype 3" profile of a recently published study on a few mycobacterial isolates phylogenetically related to M. simiae (31). The authors of that study concluded that the genotype 3 isolates (n ϭ 2) had an HPLC phenotype similar to that of M. lentiflavum, but conventional tests identified them as M. simiae.…”
Section: Discussionsupporting
confidence: 73%
“…In contrast to growth behaviour in culture, the sequence pattern was characterized by the occurrence of a short helix 18 within the hypervariable B region of the 16S rRNA gene, which is a molecular signature of fast-growing mycobacteria. These features are shared by a group of micro-organisms that includes M. simiae and other emerging mycobacterial species (Böttger et al, 1993;Kirschner et al, 1993;Meier et al, 1993;Springer et al, 1993Springer et al, , 1996Floyd et al, 1996Floyd et al, , 2000Haas et al, 1997;Tortoli et al, 1997;Herbst et al, 2001). xenopi.…”
mentioning
confidence: 99%